2022
DOI: 10.1210/clinem/dgac436
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of R-Form Verapamil Added to Ongoing Metformin Therapy in Patients with Type 2 Diabetes

Abstract: Context There is a medical need for effective insulin-independent antidiabetic drugs that have the capability to promote pancreatic β-cell function and have a low risk of hypoglycemia in type 2 diabetes mellitus (T2DM) patients. R-form verapamil (R-Vera), which is able to enhance the survival of β-cells and has higher cardiovascular safety margin compared to racemic verapamil, was developed as a novel approach for the T2DM treatment. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In collaboration with investigators from Japan and South Korea, we collected real-world data from medical records and proved that the use of sodium-glucose cotransporter 2 inhibitors was associated with lower inpatient expenses and emergency room visits compared with dipeptidyl peptidase-4 inhibitors use in routine clinical practice 13 . Recently, we examined a new form of the old drug, R-form verapamil, which could further reduce the level of glycated hemoglobin in addition to metformin therapy in patients with type 2 diabetes in Taiwan 14 .…”
Section: Explorationsmentioning
confidence: 99%
“…In collaboration with investigators from Japan and South Korea, we collected real-world data from medical records and proved that the use of sodium-glucose cotransporter 2 inhibitors was associated with lower inpatient expenses and emergency room visits compared with dipeptidyl peptidase-4 inhibitors use in routine clinical practice 13 . Recently, we examined a new form of the old drug, R-form verapamil, which could further reduce the level of glycated hemoglobin in addition to metformin therapy in patients with type 2 diabetes in Taiwan 14 .…”
Section: Explorationsmentioning
confidence: 99%
“…This randomized, double-blind, placebo-controlled clinical trial showed a significant reduction in Hb1Ac levels in patients with T2D, following treatment with verapamil ( Malayeri et al, 2021 ). It is noteworthy that co-treatment with verapamil and metformin significantly improved the glycemic control in patients with T2D by reducing HbA1c and fasting plasma glucose levels ( Wang et al, 2022 ). Applying to precision medicine, an innovative approach to tailoring disease prevention and treatment would be by taking into account the differences in genes, ethnicity, environment, and lifestyle, in order to provide a more elaborative data regarding efficacy and safety of verapamil in maintaining HbA1c level and general blood glucose management, especially in populations with diverse attributes.…”
Section: From Hypertension To Diabetes Mellitusmentioning
confidence: 99%
“…In the heart and the pancreas, effective pharmacological LTCC blockage can inhibit the expression of pro-apoptotic thioredoxin-interacting protein, a significant contributor to pancreatic β-cell dysfunction and a key gene regulated in response to hyperglycemia, thereby promoting the survival and proper functioning of β-cells and improving glucose homeostasis[ 46 , 48 ]. Verapamil has, thus, the potential not only to enhance β-cell survival and function, but also improve and even prevent overt diabetes of both types[ 48 , 49 ]. In a recent study, verapamil combined with metformin, significantly improved glycemic control in T2DM[ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Verapamil has, thus, the potential not only to enhance β-cell survival and function, but also improve and even prevent overt diabetes of both types[ 48 , 49 ]. In a recent study, verapamil combined with metformin, significantly improved glycemic control in T2DM[ 49 ]. Finally, a drawback in the use of monotherapy as ACEi/ARBs (in conditions that already are associated with low miR-155 Levels) is that they significantly further decrease already reduced miR-155 Levels[ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%